Cellular Specificity of NF-κB Function in the Nervous System - Dresselhaus, Erica C.; Meffert, Mollie K. (Frontiers in Immunology, 2019)
Nuclear Factor Kappa B (NF-κB) is a ubiquitously expressed transcription factor with key functions in a wide array of biological systems. While the role of NF-κB in processes, such as host immunity and oncogenesis has been more clearly defined, an understanding of the basic functions of NF-κB in the nervous system has lagged behind. The vast cell-type heterogeneity within the central nervous system (CNS) and the interplay between cell-type specific roles of NF-κB contributes to the complexity of understanding NF-κB functions in the brain. In this review, we will focus on the emerging understanding of cell-autonomous regulation of NF-κB signaling as well as the non-cell-autonomous functional impacts of NF-κB activation in the mammalian nervous system. We will focus on recent work which is unlocking the pleiotropic roles of NF-κB in neurons and glial cells (including astrocytes and microglia). Normal physiology as well as disorders of the CNS in which NF-κB signaling has been implicated will be discussed with reference to the lens of cell-type specific responses.